Impact of Improved Technology on Soyabean Productivity in Frontline Demonstration - Dubey, Swapnil; Tripathy, Sarvesh; Singh, Pradyumn; Sharma, R.K. (Indian Journal of Extension Education, 2011)
Krishi Vigyan Kendra, Raisen (M.P.) during the period from 2004-05 to 2008-09 conducted a total 73 frontline demonstration of soybean crop. Cultivation practices comprised under FLD viz. use of improve variety (JS-93-05), seed treatment, seed inoculation, spacing 30cm, balance application of fertilizers (20:60:20kg N:P:K per ha), weed control and plant protection measures show that percentage increase in the yield of soybean ranged from 55.26% to 80.00% over farmer’s practice. The highest seed yield 17.48 q ha-1 was recorded in the year 2008-09 in FLD, which was 80.50% more over the farmer’s practice (9.66 q ha-1). The highest extension gap which ranged from 5.25 q ha-1 to 7.82 q ha-1 during the period. The additional cost Rs. 2148 to Rs. 2348 gave additional net return, it was ranged from Rs. 4283 to Rs. 7470 per hectare with 1:1.87 to 1:3.24 incremental benefit : cost ratio.